Endocrine Evaluation in POEMS Syndrome: A Cohort Study - Yang, Hongbo; Zhao, Hao; Gao, Xuemin; Huang, Xufei; Cao, Xinxin; Zhou, Daobin; Xia, Weibo; Li, Jian (Frontiers in Endocrinology, 2020)
Endocrinopathy is an important characteristic of POEMS syndrome. However, endocrine responses to different regimens were unknown so far. Here we investigated endocrine characteristics in 383 patients with newly diagnosed POEMS syndrome and thyroid responses one year after treatment with autologous peripheral stem cell transplantation, melphalan plus dexamethasone, or lenalidomide plus dexamethasone. Overt hypothyroidism and subclinical hypothyroidism were noted in 20.6% (79/383) and 36.0% (138/383) of patients. Adrenal insufficiency was noted in 13.6% (43/316) of patients. Hyperprolactinemia was noted in 62.0% (207/330) of patients. Hypogonadism was noted in 48.0% (60/125) of female and 22.6% (51/226) of male patients. Thyroid function was significantly related with baseline risk stratification (p < 0.001) and significantly improved regardless of initial regimens. Patients with baseline hypothyroidism had a significant inferior progression-free survival (PFS) (p=0.028) and overall survival (OS) (p=0.006). Three-year PFS in patients with and without baseline hypothyroidism were 68.9% vs. 82.5% respectively. Three-year-OS in patients with and without baseline hypothyroidism were 82.8% vs. 92.8% respectively. In summary, hypothyroidism, hyperprolactinemia and hypogonadism are common endocrinopathies in POEMS syndrome. Thyroid function significantly improved regardless of the initial regimens. Thyroid function parallels with baseline risk stratification and patients with baseline hypothyroidism have significantly inferior OS and PFS.